The Film "500 Days of Summer" (2009) Movie By Marc Webb : an Individual Psychological Approach of Friends With Benefits - Bulanku Maharani; Dewi Candraningrum (EduInovasi: Journal of Basic Educational Studies, 2025)
This research discusses the phenomenon of the FWB relationship depicted in the characters Tom and Summer in the movie 500 Days of Summer. Their relationship shows complex emotional conflicts due to differences in mindset, lifestyle, and emotional needs of the two characters. This research uses Adler's individual psychology approach including the principles of superiority, inferiority, lifestyle, creative self, fictional goals, and social interest. This research uses a qualitative approach with a descriptive method, using literature study techniques for data collection. The results of this study show that Tom's dependency based on inferiority contradicts Summer's lifestyle or principles. The incongruity created stems from Tom's constant need for external validation, but Summer chooses freedom in emotional relationships and life paths. This imbalance was a major source of conflict, as Tom expected a deeper commitment, while Summer felt the pressure threatened her freedom. This research contributes to the field of individual psychology. Through the approach of Adler's principles, it offers new insights into the cause and effect in a non-committal relationship or FWB (Friends With Benefit). The results of the study provide new insights into the psychological dynamics in relationships without commitment, particularly from the perspective of Adler's theory. The mismatch of lifestyles and goals between individuals in FWB relationships can trigger deep emotional conflict. This research not only contributes to understanding individual psychology, but also opens further discussion on how films and literary works portray the complexity of human relationships. By understanding FWB relationships through this theory, this research is expected to provide a new understanding of emotional conflict and expectations in romance relationships in the modern era.